A multiscale evaluation of the surface integrity in boring trepanning association deep hole drilling. (December 2017) - Zhang, Huang; Shen, Xingquan; Bo, Arixin; Li, Yaoming; Zhan, Haifei; Gu, Yuantong
Abstract: Boring trepanning association (BTA) deep hole drilling is one of the most important manufacturing techniques to produce a large length-to-diameter ratio hole for industrial applications. In addressing the challenge of excessive surface damage, inefficiency and poor indexing in BTA deep hole drilling, for which there are limited studies reported. The functional behaviour of deep hole machining and the correlation between the machined surface quality, subsurface layer deformation and the machining conditions are investigated in this paper, together with the drilling mechanism. Various parameter combinations are used to produce different samples on which surface roughness and microstructures are studied. Metallurgical characterization is performed on the subsurface regions, followed by qualitative and quantitative mechanical nanohardness investigations. Electron microscopic analysis reveals various surface features such as grooves and plateaus, folding, material flaking that are exclusive to deep hole drilling. It has been found that improved surface integrity in BTA drilling relies on a trade-off among feedrates and speeds. Although considered sample dependent, combination of a feedrate of 28 mm min −1 and a speed of 630 r min −1 can produce nearly excellent surface integrity. Grain structure observations over the subsurface reveal three different layered zones including an ultrafine grain structure layer, a transitional grain structure layer and a substrate material layer. A significantly hardened (56% increase) surface layer on cutting-and-burnishing region comparing with the solely cutting region is detected. The subsurface grain features are induced by repeated thermo-mechanical functioning that causes grain refinement and thus materials hardening. The different surface integrities are the result of comprehensive functions of the machining parameters and combined drilling mechanism. Highlights: The cutting-burnishing effect of BTA drilling is elaborated by analyzing the drilling mechanism and surface integrity. The coordination of the guide pads, cutting edges and machining parameters produces exclusive surface features. There is an optimum combination of machining parameters for BTA drilling when machining cast iron workpiece. The machined subsurface possesses layers with grain size gradient and distinctive hardness values.